Lattice dynamics and thermal properties of CaWO4 - Senyshyn, A; Kraus, H; Mikhailik, V; Yakovyna, V (2004)
Thermodynamic properties of CaWO4 were studied using the GULP code incorporating semiclassical simulations based on quasiharmonic lattice dynamics and static lattice minimisation methods. Free energy minimization along with so called "relax" fitting was used to obtain the parameters characterising the interatomic interaction potential. From analyses of the calculated and experimental cell sizes, thermal expansion coefficients, elastic constants, phonon density of states, heat capacity, entropy, and Grüneisen parameters it is concluded that quasiharmonic lattice dynamics give a good description of these properties of CaWO4 at temperatures up to 800 K.